Prevalence and Factors Associated with Low Birth Weight and Preterm Delivery in the Ho Municipality of Ghana. (23rd February 2022) - Axame, Wisdom Kudzo; Binka, Fred Newton; Kweku, Margaret
Abstract : Background . Low birth weight and preterm delivery are birth outcomes that can predict newborns' survival, development, and long-term health outcomes. This study assessed the prevalence and factors associated with low birth weight and preterm delivery in the Ho Municipality of Ghana. Methods . This retrospective, cross-sectional study analysed data from 680 birth records between October and December 2018. Univariate and multivariate logistic regression models predicted low birth weight and preterm delivery factors. Results . The prevalence of low birth weight and preterm delivery was 12.9% and 14.1%, respectively. Increasing maternal age (AOR: 0.52; 95% CI: 0.28–0.98), multiparity (AOR: 0.54; 95% CI: 0.30–0.94) and increasing doses of sulphadoxine-pyrimethamine (AOR: 0.43; 95% CI: 0.22–0.84) significantly reduced the odds of low birth weight. However, caesarean section (AOR: 1.94; 95% CI: 0.1.16–3.27) and hypertension (AOR: 2.06; 95% CI: 1.27–03.33) significantly increased the likelihood of low birth weight. An increasing number of antenatal care visits (AOR: 0.38; 95% CI: 0.18–0.80) and doses of sulphadoxine-pyrimethamine (AOR: 0.43; 95% CI: 0.19–0.97) were significantly associated with decreased odds of preterm delivery, while caesarean section increased the odds of preterm delivery by two folds (AOR: 2.14; 95% CI: 1.15–3.99). Conclusion . This study shows that maternal age, parity, number of antenatal care visits, hypertension, SP/IPTp, and caesarean section were independently associated with low birth weight and preterm delivery. Education and interventions should be prioritised as vitally important on these factors to reduce the risk and complications associated with these birth outcomes.